Academic Supervision in Improving Teacher Professionalism - Elliana Elliana; Yusrizal Yusrizal; Nasir Usman (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to obtain empirical data about academic supervision in improving teacher professionalism at Lhokseumawe State Vocational High School. Academic supervision must be based on data, objective facts. Academic supervision is routine work that supervisors must carry out because of a dynamic curriculum that requires improvement in both documentation and contextually in the field. The method in this research uses a qualitative approach with descriptive analysis methods. The primary data sources of this study were obtained from direct interviews with informants consisting of school principals, teachers, and students, results from observations, and secondary sources obtained from various studies of documents, texts, and archives related to the implementation of Academic Supervision. The principal has carried out academic supervision in improving teacher professionalism, evidenced by the planning of supervision schedules, implementing, assessing the results of teacher performance using learning instruments prepared, and following up on the results of learning supervision. Supervision theory has been implemented well, one of which is directive supervision in learning and implementing initial meetings with teacher interviews carried out before implementing supervision.